Strength Exercises With Blood Flow Restriction Promotes Hypotensive and Hypoglycemic Effects in Women With Mellitus Type 2 Diabetes?: Randomized Crossover Study - da Silva Rodrigues, Arthur Wagner; Alves Martins, Ana Beatriz; de Albuquerque Filho, Nailton José Brandão; de Queiros, Victor Sabino; Gonçalves Assis, Marina; Batista dos Santos, Eliete Samara; Cavalcanti Cabral, Luiz Arthur; Gomes, Felippe Barbosa; Taheri, Morteza; Irandoust, Khadijeh; Rodrigues Neto, Gabriel (Health Nexus, 2023)
The aim of this study was to investigate the effects of blood flow restriction (BFR) strength exercises on blood pressure (BP) and blood glucose (BG) in diabetic women. Ten women with type II diabetes (Age = 56.9 ± 7.4 years old; BMI = 27.2 ± 4.2 kg/m2; Diagnostic time = 10.6 ± 4.1 years) participated in this study. On three non-consecutive days, participants were randomly assigned to 1 of 3 training conditions: (i) Low-load exercise [LL; ~ 20% of 1 maximum repetition (1RM)]; (ii) LL-BFR exercise [~ 20% of 1RM/50% of arterial occlusion pressure (AOP)]; (iii) High load exercise (HL; ~ 65% of 1RM). Systolic BP (SBP), diastolic BP (DBP) and mean (MBP) values ​​were assessed before, immediately, 15, 30, 45 and 60 min after the interventions. BG concentrations were analyzed before, immediately and 60 min after the interventions. SBP significantly reduced 60 min after LL exercise (p = 0.002), but it was not significantly reduced at any point after LL-BFR or HL exercise. DBP decreased significantly 45 min after LL exercise (p = 0.028) and 60 min after LL and LL-BFR exercise (p = 0.004 and p = 0.002, respectively). We verified a condition effect for the BG percentage variation, however post-hoc analyzes revealed only a difference tendency between LL and LL-BFR exercises (3.5% and -10%, respectively; p = 0.053). It is concluded that the LL and LL-BFR exercise protocols resulted in a post-exercise hypotensive effect, and the BFR protocol, apparently, presents superiority in BG reduction.